Take off in French (Oxford : Oxford University Press, 2000)
Oxford Take Off in French provides you with an innovative way of learning French. Give instruction in how to speak French.
Keywords: French language -- Self instruction; French language -- Problems, exercises, etc; French language -- Soundrecording for English speakers; French language -- Conversation and phrase books -- English